Duas novas espécies de Dryinidae (Hymenoptera: Chrysidoidea) de áreas de Mata Atlântica do Estado de São Paulo, Brasil - Martins, A. L. (2015)
Two new species of Dryinidae are described and illustrated: Dryinus auratus Martins, Lara, Perioto & Olmi sp. nov. and Gonatopus mariae Martins, Lara, Perioto & Olmi sp. nov., both from areas of Atlantic Rainforest at São Paulo State, Brazil. Keys to species are provided.